PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJAPEGAWAI DINAS KEBUDAYAAN DAN PARIWISATA KABUPATEN TIMOR TENGAH SELATAN - Godlif G. Nomleni (JI@P, 2015)
This research was intended to know the influence of leadership andmotivation toward the official performance. Reasearch was conducted atCulture and Tourism Office in Mid-South Timor Regency. Population of thisresearch were all officials working at that office. Total number of the officialwere 32. This research did not use sampling technique since all of the 32officials were observed. Questionnaire were employed as the instrument indata collection. Tests of validity and reliability of the instrument was appliedin this research. Simple as well as multiple regression analysis using SPSS16 version was manipulated to test the hypothesis. Based in research result,some conclusions can be derived: (1) there is positive influence ofleadership toward the official performance; (2) there is positive influence ofwork motivation uppon official performance; (3) there is simultaneus positiveinfluence of the leadership and of work motivation toward officialperformance. Researh result indicates that Adjusted R Square = 0,621; itmeans that the leadership and work motivation contribute simultaneously asmuch as 62,1 %. The rest, i.e. 37.9% of the official performance is influenceby variables other than the leadership and work motivation. The othervariables mentioned might be the official professionalism, carreerdevelopment, organizational culture, and others that is recommended fordoing further research in that matter.Keywords: official performance; leadership; work motivation.Pendahuluan